E-HRM: Innovation or irritation. An explorative empirical study in five large companies on web-based HRM - Huub Rüel; Tanya Bondarouk; Jan Kees Looise (Management Revue, 2004)
Technological optimistic voices assume that, from a technical perspective, the IT possibilities for HRM are endless: in principal all HR processes can be supported by IT. E-HRM is the relatively new term for this IT supported HRM, especially through the use of web technology. This paper aims at demystifying e-HRM by answering the following questions: what actually is e-HRM?, what are the goals of starting with e-HRM?, what types can be distinguished? and what are the outcomes of e-HRM? Based upon the literature, an e-HRM research model is developed and, guided by this model, five organizations have been studied that have already been on the 'e-HR road' for a number of years. We conclude that th e goals of e-HRM are mainly to improve HR's administrative efficiency/to achieve cost reduction. Next to this goals, international companies seem to use the introduction of e-HRM to standardize/harmonize HR policies and processes. Further, there is a 'gap' between e-HRM in a technical sense and e-HRM in a practical sense in the five companies involved in our study. Finally, e-HRM hardly helped to improve employee competences, but resulted in cost reduction and a reduction of the administrative burden.
Keywords: 650; Electronic Human Resource Management; Human Resource Management; Information Technology; Explorative Case Studies; Personalmanagement; Informationstechnik